2009
DOI: 10.1007/s00300-009-0632-3
|View full text |Cite
|
Sign up to set email alerts
|

Meso- and bathypelagic distribution and abundance of chaetognaths in the Atlantic sector of the Southern Ocean

Abstract: We conducted multinet sampling during winter and summer in the Southern Ocean (Atlantic sector) to investigate the eVect of water mass, season and water depth on abundance and species composition of meso-and bathypelagic chaetognaths. Eukrohnia hamata (mean 115 ind. 1,000 m ) below 1,000 m. A further six species were identiWed, among them the rare bathypelagic species Heterokrohnia fragilis and the subtropical Eukrohnia macroneura that is new to the Antarctic. Water depth and season were the principal determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 30 publications
(44 reference statements)
0
34
0
Order By: Relevance
“…However, E. hamata was the most abundant in all areas (up to 95% of all chaetognaths), whereas the contribution of other species depended on the location and the study season. Kruse et al (2009), investigating the Lazarev Sea in summer and winter, suggested that chaetognath abundance and species composition were affected by several parameters: water mass, water depth, season and ontogenesis, with the effect of water depth considered to be the major determinant. A similar trend was observed by Alvarino (1964), Bielecka and Żmijewska (1993), Błachowiak-Samołyk et al (1995), Duro et al (1999), Duro and Gili (2001), and Kulagin (2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, E. hamata was the most abundant in all areas (up to 95% of all chaetognaths), whereas the contribution of other species depended on the location and the study season. Kruse et al (2009), investigating the Lazarev Sea in summer and winter, suggested that chaetognath abundance and species composition were affected by several parameters: water mass, water depth, season and ontogenesis, with the effect of water depth considered to be the major determinant. A similar trend was observed by Alvarino (1964), Bielecka and Żmijewska (1993), Błachowiak-Samołyk et al (1995), Duro et al (1999), Duro and Gili (2001), and Kulagin (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The species number varies from a few to ca. 30 in a given region, and is higher at lower latitudes (Alvarino 1964;Terazaki 1998;Ulloa et al 2000;Pierrot-Bults 2008;Kruse et al 2009). Due to their relatively low tolerance to changes in hydrological conditions, many species, including the endemic Antarctic species P. gazellae, are considered good indicators on various water masses (O'Sullivan 1982;Pierrot-Bults 2008).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations